Evaluasi Kualitas Layanan Billing Information System Rumah Sakit dengan Metode ServQual (Studi Kasus Pada RSUD Dr. Murdjani Sampit Kabupaten Kotawaringin Timur Provinsi Kalimantan Tengah) - Abertun Sagit Sahay; Eko Nugroho; Wing Wahyu Winarno (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
To meet customer satisfaction, organizations must figure out what customers want. Customer satisfaction is one of the factors or of the measure of success for any development and implementation of information systems in an organization. Dr. Murdjani Hospital of Sampit, Kota Waringin Timur Regency of Central Kalimantan Province develops and implements a Billing Information System service which integrates all service activities into a system that records all financial transactions. By performing this measurement, the hospital can figure out every single aspect of the service needing special attention for the purpose of improvement, and all parties are satisfied with the services provided. Evaluation of quality of Billing Information System service of Dr. Murjani Hospital using ServQual method has 5 (five) dimensions of customer satisfaction that includes tangible, reliability, responsiveness, assurance and empathy. The results are the 5 (five) dimensions each of which affects significantly customer satisfaction, and they are reliability tangible, assurance, empathy and responsiveness.